Laminin-Modified Dental Pulp Extracellular Matrix for Dental Pulp Regeneration - Fu, Jiahui; Chen, Jianfeng; Li, Wenjun; Yang, Xiaomin; Yang, Jingyan; Quan, Huixin; Huang, Haitao; Chen, Gang (Frontiers in Bioengineering and Biotechnology, 2021)
Native dental pulp extracellular matrix (DPEM) has proven to be an effective biomaterial for dental pulp regeneration. However, as a significant extracellular matrix glycoprotein, partial laminins were lost during the decellularization process, which were essential for odontoblast differentiation. Thereby, this study investigated the feasibility of LN supplementation to improve the surface of DPEM for odontoblast layer regeneration. The influences of laminin on cell adhesion and odontogenic differentiation were evaluated in vitro. Then, we fabricated laminin-modified DPEM based on the physical coating strategy and observed the location and persistency of laminin coating by immunofluorescent staining. Finally, laminin-modified DPEM combined with treated dentin matrix (TDM) was transplanted in orthotopic jaw bone of beagles (n = 3) to assess the effect of LNs on dental pulp tissue regeneration. The in vitro results showed that laminins could improve the adhesion of dental pulp stem cells (DPSCs) and promoted DPSCs toward odontogenic differentiation. Continuous odontoblastic layer-like structure was observed in laminin-modified DPEM group, expressing the markers for odontoblastogenesis, dentine matrix protein-1 (DMP-1) and dentin sialophosphoprotein (DSPP). Overall, these studies demonstrate that the supplementation of laminins to DPEM contributes to the odontogenic differentiation of cells and to the formation of odontoblast layer in dental pulp regeneration.